(untitled) (Baghdad Science Journal, 2016)
The molluscum contagiosum virus (MCV) is a dermatotropic poxvirus. The causative agent of molluscum contagiosum (MC) is nonlethal, common and worldwide. Additionally, little inflammation is associated with MC papules. The present study aims to evaluate the immune status of MC patients by measuring the level of immunoglobulins IgG and IgM by using the radial immune diffusion assay (RIA) and the level of interleukin 18 receptor 1 (IL-18R1) by the Enzyme-linked immunosorbent assay (ELISA).The study is conducted during November 2013 to April, 2014 in outpatient clinic of Baquba Teaching Hospital. There are 75 patients, diagnosed with clinical lesions of MCV on different areas of the body, whose age is ranged between 2-50 years including 40(53.3%) males and 35(46.7%) females. The study includes 15 healthy persons age between 2-50 years. The level of IL 18R1 were significantly elevated in patients (677.15±874.22) compared with control (178.46±31.79 ng/ml). There is also a significant elevation in the mean level of serum IgM, where it is 1946.6±825.6 mg/dl while in control group is 140.1±68.7mg/dl. By contrast in patients with lower levels of IgG than the control, the mean serum IgG level in patient is 221.9±96.7 mg/dl while in the control is 1229.9±299.7 mg/dl. Finally, there is no significant difference between MC patients from rural area and urban area.